Answer :
Answer:
[tex]2x^2+3x[/tex] is the expression which is equivalent to [tex]x\left(2x+3\right)[/tex].
In other words:
[tex]x\left(2x+3\right)=2x^2+3x[/tex]
Step-by-step explanation:
Given the expression
[tex]x\left(2x+3\right)[/tex]
solving
[tex]x\left(2x+3\right)[/tex]
[tex]\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b+c\right)=ab+ac[/tex]
[tex]a=x,\:b=2x,\:c=3[/tex]
[tex]=x\cdot \:2x+x\cdot \:3[/tex]
[tex]=2xx+3x[/tex]
[tex]=2x^2+3x[/tex] ∴ [tex]2xx=2x^2[/tex]
Thus,
[tex]x\left(2x+3\right)=2x^2+3x[/tex]
Therefore, [tex]2x^2+3x[/tex] is the expression which is equivalent to [tex]x\left(2x+3\right)[/tex].